COVID-19, people with disabilities, and the Italian government recovery: investigating the impact and promoting psychological resources to prevent future emergencies - Camussi, Elisabetta; Meneghetti, Daria; Sbarra, Maria Luisa; Rella, Riccardo; Barillà, Francesca; Sassi, Cinzia; Montali, Lorenzo; Annovazzi, Chiara (Frontiers in Psychology, 2023)
Introduction Given its profound and transversal impact, the COVID-19 pandemic in 2020 marked a deep point of division in how people make sense of the world and their lives. The consequences of this event were remarkable, especially for populations already facing vulnerability, exclusion, and discrimination. In Italy, over 3 million people (5.2% of the entire population) have a disability due to health issues or severe limitations that prevent them from performing daily activities. Although the COVID-19 health emergency aggravated and amplified these problems, research and studies investigating the incidence of psychological distress and the role of psychological resources for people with disabilities in the aftermath of the pandemic are still to be implemented. For these reasons, the Department of Psychology conducted a study on behalf of the Italian Government to assess the impacts of the COVID-19 pandemic on the social, psychological, and economic wellbeing of Italians with disabilities. Methods The aim was to assess the consequences of the pandemic on this population, especially the impacts related to the lockdowns and preventive measures, and to evaluate the protective role that could be played by psychological resources such as resilience, future orientation, and career adaptability in a Life Design perspective. With the collaboration of local, regional, and national associations for people with disability, an anonymous, online self-report questionnaire was distributed to 403 persons with disabilities in Italy. Results Results showed a strong relationship between the levels of psychological resources and life satisfaction during the COVID-19 pandemic. Discussion In line with studies in international literature regarding the effects of the COVID-19 pandemic on people with disabilities, this research highlights the extension of this period’s impacts on this population’s psychological wellbeing. Moreover, this study amplifies the urgent call for action and research in promoting Life Design psychological resources, given their positive and protective role in preserving and increasing people’s wellbeing.